Pengaruh Kualitas Produk dan Promosi Terhadap Kepuasaan Pelanggan Street Boba Cabang Rawamangun Jakarta Timur - Siti Nurazizah; Etika Sabariah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of product quality and promotion on customer satisfaction. The research method adopted was quantitative with a survey approach through distribution of questionnaires to 71 respondents. The data were analyzed using multiple linear regression to find out the relationship between the independent variable (product quality and promotion) the dependent variable (customer satisfaction). The results of the study show that product quality has a positive and significant influence on customer satisfaction, while promotion also has a positive but insignificant influence. The findings indicate that product quality is a major factor in shaping customer satisfaction, while promotion plays a supporting role. The study provides implications for companies to focus more on improving product quality in order to retain and improve customer satisfaction.